Pengembangan Manajemen Perpustakaan sebagai pusat informasi dan pendidikan di STAIMA Al-Hikam Malang - setiawan setiawan; Lailatul Qodariyah (STAI Ma'had Aly Al-Hikam Malang, 2019)
The development of Library Management as an information center is important because the development of good library management will be able to support the learning process, the development of management in the library has a reference that is planing, organizing, actuating and controlling. Establishment of POAC Reference certainly does not want a stagnant library in Management Development, but POAC Reference wants Development in Library ManagementThe research method used is descriptive analytical research method. that is to say some possibilities to solve the actual problem by collecting data, compiling, or classifying it, analyzing and interpreting it. The object of research is the Library of the Islamic High School Library (STAIMA) Aly Al-Hikam Malang The results of the study stated that the STAIMA Al-Hikam Malang Library in the development of Library Management has an advanced program in the next 5-10 years, namely: 1. Management of services using the Loan (delivery order) model and repayment via Drop Box or delivery order applications, Extension through Mandiri website, service is open 24 hours nonstop. 2. Management Development in the Information Technology Section, namely increasing digital collections. 3. Security System with Big data, Anti-virus, digital preservation, RFID. The aim of the research measures so far about libraries as information centers to support education by having library management that is not only stagnant but has a better management development program